Identities in transit: the (re)connections and (re)brandings of Berlin's municipal railway infrastructure after 1989. (October 2015) - Merrill, Samuel
Abstract: This article analyses urban railway infrastructures as landscapes in order to reveal their role as constructions and constructors of collective and individual identities. It does this by introducing the notion of 'identities in transit', a rhetorical category that problematises the tendency to consider the nexus of urban infrastructure and identity formation only during discrete moments and in relation to abstract subjectivities. Specifically, it explores the (re)connections and (re)brandings that Berlin's municipal railway infrastructure, the Stadtschnellbahn (S-Bahn) and Untergrundbahn (U-Bahn), experienced in the years surrounding the fall of the Berlin Wall, and considers their contribution to the formation of post-unification municipal identities. These discussions are historicised and contextualised by an account of the consequences of Berlin's Cold War division on its transport infrastructure. The article then considers the subsequent impact of the city's reunification and how the S- and U-Bahn became a means of constructing more unified municipal identities. It considers the process by which Berlin's municipal railway networks were reconnected after November 1989 and frames this process as a metaphor for both the different durations and protracted process of the city's reunification and the identities these gave rise to. Thereafter, the article argues that the rebranding strategy pursued by one of the city's municipal transport authorities provides one of the earliest examples of an attempt to manufacture a unified identity for the New Berlin. The article highlights that while processes at the municipal level emphasised the unification of collective identities, experiences of the infrastructures themselves often involved persisting divides and forms of subversion and social conflict that highlighted the meeting of more diverse individual identities. Highlights: Examines infrastructural landscapes as constructions and constructors of identity. Shows how Berlin's railways have helped create divided and reunified identities. Shows that while authorities stressed unification divides persisted in daily life. Analyses rail identities beyond nationality, single events and abstract characters.